STRATEGI PENGEMBANGAN OBJEK WISATA AIR TERJUN GURUH GEMURAI DESA KASANG KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Nurfithriani Ridwan; Nursiah Chalid; Nobel Aqualdo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The study is done in the village kasang subdistrict kuantan mudik regency kuantan singingi .Research is expected could be beneficial as an ingredient of studies and information for next researchers that deals with the same problems and research was beneficial as fikiran contributions and information as well as material consideration for parties who want to develop tourism objects a waterfall guruh gemurai. This research using analysis SWOT. The population in this research was all who did tourism activity in tourism object waterfall guruh gemurai.Sample in this research using methods Accidental Sampling and the sample is 100 respondents. Based on the results of research shows that the analysis SWOT conducted the value of the acquired - weakness: 2,3-0,65 = 1.7 and as a threat: 2,06-0.67 = 1,39.The use of alternative strategies (Strength and Opportunities) in consideration that tourism guruh gemurai have a voice of the waterfall the many and great to be developed, however, has not been optimally be used to develop the tourism waterfall in peals of guruh gemurai to create a strategy of using the power ( strength ) in order to take advantage of the opportunities.Keywords : development strategy, Attraction and analysis SWOT